Pengembangan Paket Pembelajaran Penanganan Pascapanen Buah-Buahan Kelas XI Semester II SMK-PP Negeri Banjarbaru - Resvathi Swastika Ayu Perdana; I Nyoman Sudana Degeng; Dedi Kuswandi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
This research and development aims to produce a postharvest handling learning package for class XI semester II consisting of teaching materials, teacher guides, student guidance funds as an effort to solve learning problems at SMK-PP Banjarbaru TPH Expertise Program. This learning package uses the Dick and Carey model. The results of expert validation and field trials show that the learning package meets very feasible qualifications. The use of learning packages can also improve student learning outcomes. This can be seen from the increase in post-test and pretest scores by 46%.